2019
DOI: 10.26689/itps.v2i1.499
|View full text |Cite
|
Sign up to set email alerts
|

Schiff Base Oxime Derivatives Reactivate Chlorpyrifos-induced Acetylcholinesterase Inhibition

Abstract: Background: The biological effects of organophosphorus (OP) compounds are connected with the irreversible inhibition of acetylcholinesterase (AChE), an important neuromediator acetylcholine (ACh) splitting enzyme in the human body at the synaptic clefts. Due to this inhibition, AChE is unable to fulfil its physiological function resulting in the accumulation of ACh, which, in turn over stimulates the parasympathetic nerve receptors, and causes fatal cholinergic crisis. Objective: The objective of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Authors used the formulations from natural polymers/gums and have shown a promising delivery system which can enhance the bioavailability and has potential for greater therapeutic efficacy. The second article by Katagi et al worked on "Schiff Base Oxime Derivatives Reactivate Chlorpyrifos-induced Acetylcholinesterase Inhibition" [2]. This study is primarily aimed at synthesizing a series of Schiff base oximes and assessing the in vitro reactivating potency against chlorpyrifosinhibited acetylcholinesterase.…”
mentioning
confidence: 99%
“…Authors used the formulations from natural polymers/gums and have shown a promising delivery system which can enhance the bioavailability and has potential for greater therapeutic efficacy. The second article by Katagi et al worked on "Schiff Base Oxime Derivatives Reactivate Chlorpyrifos-induced Acetylcholinesterase Inhibition" [2]. This study is primarily aimed at synthesizing a series of Schiff base oximes and assessing the in vitro reactivating potency against chlorpyrifosinhibited acetylcholinesterase.…”
mentioning
confidence: 99%